PERANCANGAN ANIMASI 3D EDUKATIF TENTANG MODUS PENIPUAN WHATSAPP DENGAN METODE MDLC: Studi Edukatif Menggunakan Pendekatan Multimedia Development Life Cycle (MDLC) - Putra Kang, Anugerah; Fauzi, Rahmat (Computer Science and Industrial Engineering, 2025)
Phishing scams on WhatsApp have become increasingly common, targeting users with deceptive messages to steal personal data. To help address this issue, this study presents the design of a 3D educational animation developed using the Multimedia Development Life Cycle (MDLC) framework, which consists of concept, design, material collection, assembly, testing, and distribution stages. The animation aims to raise awareness among young social media users, especially those aged 15–25, who are considered highly vulnerable to such threats. The animation was published on YouTube and evaluated through both audience feedback and a Likert-scale questionnaire distributed to 25 respondents. Within 28 days, the video gained 456 views, 77 likes, and 122 comments, reflecting a positive initial reception. The questionnaire yielded an average score of 4 out of 5, indicating favorable responses regarding animation quality, character design, and message clarity. Technical assessments using MediaInfo and VLC Media Player confirmed the animation’s smooth performance in terms of visuals and audio. Overall, the results demonstrate that the 3D animation effectively delivers educational content and has the potential to serve as a useful media tool to increase public understanding of phishing tactics on messaging platforms